NATIONAL INNOVATION SYSTEMS: INTERNATIONAL PRACTICES IN THE MANAGEMENT OF INNOVATION ACTIVITIES - YEMCHENKO, Maksym (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In today’s globalized world, national innovation systems (NIS) play a key role in ensuring the competitiveness of countries and their economic development. The concept of NIS, their importance, main components and analysis of world examples of successful innovation systems were studied. NIS is defined as a network of institutions in the public and private sectors whose activities and interactions initiate, import, modify and disseminate new technologies. The importance of NIS is based on their ability to stimulate innovation, increase labor productivity, create new jobs and ensure sustainable economic growth. It is noted that the main structural component of NIS is the government, which forms innovation policy and provides financing; educational and scientific institutions that generate knowledge and train qualified personnel; an innovative business sector; innovation support infrastructure (technology parks, business incubators, venture funds); and the legal system protecting intellectual property. World examples of successful NIS were analyzed, in particular, Anglo-Saxon, Asian, Euro-continental and Scandinavian models. It was determined that each of them has a unique approach to the construction of NIS and reflects their historical, cultural and economic characteristics, the Anglo-Saxon model is characterized by a high level of competition and a significant role of the private sector, while the Asian model is characterized by close cooperation between the government and business. The study shows that there is no universal NIS model that would be suitable for all countries. It is noted that each state should develop its own innovation system, taking into account its strengths and specifics, taking into account the best successful world practices. It is emphasized that an effective NIS is a key factor for the long-term economic success of the country in the conditions of global competition. Further research could be aimed at examining the impact of digitization and global challenges, such as climate change, on the development of NIS.